THE CONCEPT AND EVOLUTION OF INTONATION: ITS HISTORY, STRUCTURE, AND SIGNIFICANCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of intonation, focusing on its historical development, functions, and structural components. It delves into how intonation, through variations in pitch, stress, rhythm, and tone, contributes to the grammatical, discourse, and expressive aspects of language. The historical section highlights key contributors to the study of intonation, such as Aristotle, Henry Sweet, and Kenneth L. Pike, while emphasizing the advancements made in the 20th century with technological tools. Additionally, the article examines cross-linguistic variations, contrasting the roles of intonation in tonal and non-tonal languages. The conclusion underscores the significance of intonation in communication, from emotional expression to technological applications, offering insights into its role in fostering human connection and understanding.